Introduction to the new mainframe z/OS basics - Ebbers, Mike; O'Brien, Wayne; Ogden, Bill (IBM redbooks, 2006)
This IBM Redbook provides students of information systems technology with the background knowledge and skills necessary to begin using the basic facilities of a mainframe computer. It is the first in a planned series of textbooks designed to introduce students to mainframe concepts and help prepare them for a career in large systems computing. For optimal learning, students are assumed to have successfully completed an introductory course in computer system concepts, such as computer organization and architecture, operating systems, data management, or data communications. They should also have successfully completed courses in one or more programming languages, and be PC literate. This textbook can also be used as a prerequisite for courses in advanced topics or for internships and special studies. It is not intended to be a complete text covering all aspects of mainframe operation, nor is it a reference book that discusses every feature and option of the mainframe facilities. Others who will benefit from this course include experienced data processing professionals who have worked with non-mainframe platforms, or who are familiar with some aspects of the mainframe but want to become knowledgeable with other facilities and benefits of the mainframe environment. As we go through this course, we suggest that the instructor alternate between text, lecture, discussions, and hands-on exercises. Many of the exercises are cumulative, and are designed to show the student how to design and implement the topic presented. The instructor-led discussions and hands-on exercises are an integral part of the course material, and can include topics not covered in this textbook. This book is also offered with a textbook cover instead of a redbook cover in PDF and hardcopy formats. Download PDF of book with textbook cover (6.0MB) Order hardcopy of book with textbook cover Note: The contents of the book are identical in both the textbook and redbook versions except for the covers.